PERAN GAYA KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH MOTIVASI INTRINSIK DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri Di Kecamatan Pati Kabupaten Pati) - Hasnawati, 12.52.02.0218; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is intended to examine the influence of motivation intrinsic and emotional intelligence to the state senior high school teachersâ work performance with the moderation of transformational leadership style. The specific purpose of this research is to examine the role of transformational leadership style moderates the influence of intrinsic motivation and emotional intelligence to the teachersâ work performance. The usage of this research is to explain and expand the previous research about the role of transformational leadership style moderates the influence of intrinsic motivation and emotional intelligence to the teachersâ work performance. This research used the population of 116 teachers of state senior high school in Pati District, Pati Regency. The technique of sample collection used in this research is non-probability sampling with the purposive method. The analysis technique used in this research is regression model moderate quasi. Based on the research result can be conduded that: intrinsic motivation influences teachersâ work performance, emotional intelligence influences the teachersâ work performance, transformational leadership style do not moderate the influence of intrinsic motivation to teachersâ work performance, , transformational leadership style strengthen the influence of emotional intelligence to the teachersâ work performance.Keywords: Intrinsic Motivation, Emotional Intelligence, Transformational Leadership Style, Teachersâ Work Performance